Productive Economic Empowerment Of PKK Women Through Tali Kur Handicrafts Based On Dayak Local Wisdom In Desa Sungai Ukoi Kecamatan Sungai Tebelian Kabupaten Sintang - Kurniati, Agusta; Parida, Lusila; Oktaviani, Ursula Dwi; Febriani, Melly; Sari, Dea Agnes Singgar (STKIP Singkawang, 2025)
As a community organization, the Family Welfare Empowerment (PKK) has the task of empowering women and families in villages. The issues related to the empowerment of productive economy of PKK groups in Sungai Ukoi village based on information data include: a) Lack of knowledge about productive economy; b) Conflicts with PKK activities due to busy schedules; c) Lack of awareness; d) Limited funds and tools to support PKK activities; e) PKK programs at the village level have not had a concrete impact on the community; f) PKK programs have not been effectively implemented; g) The implementation of PKK programs has not met the needs to prosper the community. This community service activity aims to develop the skills of the PKK women's group in the field of handicrafts based on the local wisdom of the Dayak tribe, as well as skills in marketing the products they have created, so that the PKK women’s group becomes a productive group in the economic field. The benefits of this program for the PKK mothers' group in terms of social economy for the needs of the broader community are a form of skill development and self-potential in creating cord products as well as in marketing, so that the results obtained can help the family economy. In addition, it also impacts the fulfillment of the obligations of every responsible citizen in the preservation of culture. The results of this community service activity include: an increased understanding of participants regarding handicrafts made from cord based on the local wisdom of the Dayak tribe, and an increased awareness of entrepreneurship in productive economy through product marketing materials, which leads to income from sold products.Pemberdayaan Ekonomi Produktif Kerajinan Tangan Tali Kur Berbasis Kearifan Lokal Suku Dayak Pada Kelompok Ibu-Ibu PKK Desa Sungai Ukoi Kecamatan Sungai Tebelian Kabupaten SintangABSTRAKSebagai organisasi kemasyarakatan PKK memiliki tugas memberdayakan perempuan dan keluarga di desa. Adapun permasalahan yang berkaitan pemberdayaan ekonomi produktif kelompok PKK di desa Sungai Ukoi berdasarkan informasi data meliputi: a) Kurangnya pengetahuan tentang ekonomi produktif; b) Kesibukan yang bentrok dengan kegiatan PKK; c) Kurangnya kesadaran ; c) Keterbatasan dana dan alat untuk menunjang kegiatan PKK; d) Progran PKK Desa belum berdampak konkret bagi masyarakat; e)Program PKK belum berjalan efektif; f) Pelaksanaan program PKK belum memenuhi kebutuhan untuk mensejahterakan masyarakat. Kegiatan PKM ini bertujuan mengembangkan keterampilan kelompok Ibu-ibu PKK dalam bidang kerajinan tangan berbasis kearifan lokal suku Dayak serta keterampilan dalam memasarkan produk yang telah dibuat sehingga kelompok Ibu- ibu PKK menjadi kelompok produktif dalam bidang ekonomi. Manfaat program ini bagi kelompok ibu- ibu PKK dari segi sosial ekonomi bagi kebutuhan masyarakat luas adalah bentuk pengembangan keterampilan potensi diri dalam menciptakan produk tali kur maupun dalam pemasaran sehingga hasil yang dipeoreleh dapat membantu perekonomian keluarga selain itu juga berdampak pada pemenuhan kewajiban setiap warga negara yang bertanggungjawab dalam pelestarian budaya. Hasil dari kegiatan PKM ini berupa: peningkatan pemahaman peserta terhadap Kerajinan Tangan Tali Kur berbasis kearifan local suku Dayak, dan peningkatan kesadaran berwirausaha dalam Ekonomi Produktif melalui materi pemasaran produk mendapat penghasilan dari produk yang sudah terjual.Kata Kunci :Ekonomi Produktif; Kerajinan Tangan; Tali Kur; Kelompok PKK